Perubahan Jaringan Hati Ikan Pari Kembang ( DASYATISKUHLI) Akibat Merkuri (HG) - Tresnati, Joeharnani; Trijuno, Dody Dharmawan; Djawad, Iqbal (Hasanuddin University, 2014)
Blue Spotted Ray (Dasyatis kuhlii) as the demersal organisms has a lot of accumulation of pollutants in the water that settles to the bottom. This study was conducted to look at the liver tissue alteration of Blue Spotted Ray caused by contamination of mercury (Hg). Performed on 5 tanks. Tank A as a control, tank B with concentration 0.025 ppm, tank C with concentration of 0.05 ppm, tank D with concentration 0.1 ppm and tanks E with concentration 0.2 ppm. The result is alteration on the liver tissue in the form of atrophy, cloudy swelling, vacuolization degeneration and even necrosis or death of liver tissue already. The alteration can reduce and eveneliminate the function of the liver as a toxin absorbent and can lead to death.